Blast Mines: Physics, Injury Mechanisms And Vehicle Protection. Issue 4 (1st December 2009) - Ramasamy, Arul; Hill, AM; Hepper, AE; Bull, AMJ; Clasper, JC
Abstract : Since World War II, more vehicles have been lost to land mines than all other threats combined. Anti-vehicular (AV) mines are capable of disabling a heavy vehicle, or completely destroying a lighter vehicle. The most common form of AV mine is the blast mine, which uses a large amount of explosive to directly damage the target. In a conventional military setting, landmines are used as a defensive force-multiplier and to restrict the movements of the opposing force. They are relatively cheap to purchase and easy to acquire, hence landmines are also potent weapons in the insurgents' armamentarium. The stand-off nature of its design has allowed insurgents to cause significant injuries to security forces in current conflicts with little personal risk. As a result, AV mines and improvised explosive devices (IEDs) have become the most common cause of death and injury to Coalition and local security forces operating in Iraq and Afghanistan. Detonation of an AV mine causes an explosive, exothermic reaction which results in the formation of a shockwave followed by a rapid expansion of gases. The shockwave is mainly reflected by the soil/air interface and fractures the soil cap over the mine. The detonation products then vent through the voids in the soil, resulting in a hollow inverse cone which consists of the detonation gases surrounded by the soil ejecta. It is the combination of the detonation products and soil ejecta that interact with the target vehicle and cause injury to the vehicle occupants. A number of different strategies are required to mitigate the blast effects of an explosion. Primary blast effects can be reduced by increasing the standoff distance between the seat of the explosion and the crew compartment. Enhancement of armour on the base of the vehicle, as well as improvements in personal protection can prevent penetration of fragments. Mitigating tertiary effects can be achieved by altering the vehicle geometry and structure, increasing vehicle mass, as well as developing new strategies to reduce the transfer of the impulse through the vehicle to the occupants. Protection from thermal injury can be provided by incorporating fire resistant materials into the vehicle and in personal clothing. The challenge for the vehicle designer is the incorporation of these protective measures within an operationally effective platform.